The effect of two generic aerobic interval training methods on laboratory and field test performance in soccer players - da Silva, J. F.; Nakamura, F. Y.; Carminatti, L. J.; Dittrich, N.; Cetolin, T.; Guglielmo, L. G. A. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to compare the effects of 2 generic aerobic training models, based on peak running velocity in Carminatti's test (PVT-CAR) in U-20 elite soccer players. Seventeen soccer players (age: 17.9 ± 1.0 years; 178.6 ± 5.0 cm; 73.6 ± 6.6 kg; 11.1 ± 1.3%) from a team competing in a national junior league took part in the study. The athletes performed a series of pre- and posttraining tests (incremental test on a treadmill to determine the maximal oxygen uptake [VO2max], velocity at maximal oxygen uptake [vVO2], the lactate threshold [LT], and T-CAR). The interval training models applied were with 180° direction change (T12:12; n = 9) and without direction change (T6:6; n = 8). No significant interaction (time vs. group) was observed for the majority of variables analyzed (p > 0.05), although significant main effects in time were evident regarding peak treadmill velocity (PVTREAD) (F = 56.3, p < 0.0001), vVO2max (F = 35.8, p < 0.0001), LT (F = 57.7, p < 0.0001), and PVT-CAR (F = 52.9, p < 0.0001). Moreover, there was no significant change in VO2max between pre and posttraining period (F = 4.26, p = 0.056) in both training groups. Thus, it can be concluded that the prescribed training with and without direction change in the intensity of the PVT-CAR increases the PVTREAD, the vVO2max, the LT, and the PVT-CAR similarly.